Superinnervation enhances the dendritic branching pattern of the Mauthner cell in the developing axolotl - Goodman, LA (J Neurosci, 1988)
Mauthner cells (M-cells) occur as a pair of large, uniquely identifiable neurons at ear level in the hindbrain of premetamorphic amphibians. Each receives synapses from the ipsilateral vestibular nerve (nVIII); these morphologically distinctive terminals, or club endings, are confined to the proximoventral surface and branches of the M-cell lateral dendrite. We have superinnervated this portion of the M- cell to examine the extent to which forming afferent contacts regulate the growth and branching of the lateral dendrite. Superinnervation was brought about in the developing axolotl (Ambystoma mexicanum) by unilaterally implanting an extra vestibular primordium rostral to the in situ one. The contralateral side served as control. When the larvae reached 21 mm in length, the ectopic nerve was labeled with HRP. Subsequent microscopic examination revealed that the grafts developed into anatomically normal ears. The HRP-labeled ectopic axons entered the medulla at the level of nV and confined to the nVIII tract, coursed caudad toward the ipsilateral M-cell. Electron microscopic analysis demonstrated labeled club endings on the appropriate region of the M- cell lateral dendrite. The number of club endings on experimental M- cells was significantly greater than that on the contralateral controls, and the extra terminals appeared to be distributed randomly among unlabeled ones. Comparison of reconstructed experimental and control M-cells revealed that superinnervation produced a localized enhancement of dendritic branching in the region receiving the extra nVIII synapses. In the donor embryos (those from which the vestibular primordium was removed), M-cells were unilaterally deprived of nVIII afferents. Comparison of reconstructed experimental and control M-cells in 21 mm donor larvae demonstrated that deprivation produced a localized decrease of dendritic surface in the region that normally receives nVIII synapses. Together, these data show that ingrowing axons stimulate dendritic growth and thus regulate the development of a normal dendritic branching pattern on target neurons.